EFFECT OF PLANTING METHOD AND SPRAYING WITH THE ORGANIC NUTRITION SOLUTION ON GROWTH AND YIELD OF TWO RADISH VARIETIES (RAPHANUS SATIVUS L.) - Abdullah M. S. AL-Dabbagh (Mesopotamia Journal of Agriculture)
This study was conducted in vegetable field of Horticulture Department /college of Agric. and forestry / Mosul University during the winter season of 2017-2018, to study the effect of two methods of planting (plots and furrows), and spraying with different concentration levels: 0, 3, and 6 ml.l-1 of nutritious organic solution, Tecamin Max, on the growth and production of two varieties of radish, red Celesta, and black Rudi.The results have showed a significant of furrows method as compared to the plot method when it comes to the majority of the studied characteristic, including: leaves area, the length and diameter of the root, the dry weight of the roots, the weight of the single plant, and the total yield. As for spraying with the nutritious organic solution, Tecamin Max, with 3ml.l-1 concentration levels, it showed a significant advantage regarding comparison in the length and diameter of root. The black varieties was advantageous when it came to dry root weight, while the red was advantageous in the weight of the single plant, the total yield, and the root length. Dual and triple interaction have also matched single interaction of each factor, with the triple interaction of furrow planting, while spraying with 3ml.l-1 of Tecamin Max for the red varieties providing the highest ratio of the single plant of 171.6g, and the highest total of roots of 22.88 t.ha-1.